Effective Strategies Employed by School Teachers to Promote Students’ Critical Thinking Skills - Widiastuti, Ida Ayu Made Sri; Krismayani, Ni Wayan; Murtini, Ni Made Wersi (FKIP Universitas Lampung, 2022)
Developing students’ critical thinking skill is highly important nowadays to provide students’ skills in encountering various challenges in their life. Objectives: This study investigates the strategies employed by teachers during the teaching and learning processes to promote students’ critical skills. Methods: This study used a qualitative research approach conducted in a senior high school consisting of 50 teachers and 5 teachers were selected as the participants of this research. The data were collected by conducting semi-structured interviews and the data were analyzed descriptively. Findings: This study found several strategies employed by the teachers in enhancing students’ critical thinking skills. Conclusions: the Findings of this study provide implications to enrich the body of knowledge relevant to the theories concerning effective strategies to develop students’ critical thinking skills. Keywords: strategy, teachers, promote, critical, skill.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202209